The Influence of Relationship Marketing, And Green Marketing Toward Business Sustainability On Msmes Kab. Bandung. - Dwi Rachmawati; Zalena Mohd; Suci Ayu Sudari; Cyka Oktaviani (International Publisher, 2023)
This study aims to find out the influence of Relationship Marketing, and Green Marketing to the Sustainability Business on SMEs (small and medium-scale Enterprise) in Kab. Bandung. Finding relation between variables allows this study to find the best strategy marketing to maintain the sustainability business of SMEs in Kab. Bandung. With the number of respondents as many as 100 SMEs, the instrument in the questionnaire is measured using a Likert scale (5 scales) then the data was processed with SPSS, while the variables are 1) Independent Variables consisting of Relationship Marketing, Green Marketing, 2) Dependent Variable is Sustainability Business. The used analysis in this study is multiple regression. The results show that Realtionship Marketing and green marketing has a positive and significant effect on Sustainability Business. The study discusses the results and give constructive suggestions for maintaining the sustainability business of SMEs.